UPAYA PENINGKATAN PRODUKSI JAGUNG BERBASIS ASPEK KESUBURAN TANAH DI KECAMATAN SIMPANG RAYA - Hidayat Arismunandar Katili; Rahmawati Sayedi; Dian Puspapratiwi; Ilham Ladonu (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Corn is an agricultural commodity that specializes in food crops that are cultivated as the mainstay of the people of Simpang Raya District, which is used as a staple food to replace rice. But, the main obstacle is that the corn production obtained is not optimal. This is because the corn cropland has not been managed properly, one of which is in terms of soil fertility. Therefore, efforts are needed to increase optimal production by evaluating soil fertility in the Corn crop area in Simpang Raya. This research was carried out in Simpang Raya District from June to October 2022, where the activity was to conduct a survey and soil sampling in 5 locations that were chosen intentionally and were considered to be representative of the entire corn cropland in Simpang Raya District. The criteria for assessing soil fertility on corn cropland at the research location are adjusted to the determination of soil fertility status referring to the Soil Research Center. After that, it will be adjusted using the matching method between the quality of the land obtained with the condition that the growing criteria for corn crops refer to the Center for Research and Development of Agricultural Land resources. The results showed that soil fertility in corn cropland is classified as low. Furthermore, the determination of soil fertility based on the criteria of the corn crop as a whole obtained marginal status. This is because the content of KB, P2O5, and K2O in the corn fields representing the research area is relatively low. so, the need for land management by providing organic matter and intensive fertilization so that the soil fertility status of corn land in Simpang Raya District can increase and meet the nutrient needs of corn plants, that way the corn crop will get optimal production results